2019
DOI: 10.1002/anie.201912733
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐Nanoplated CoS@TiO2 Nanofibrous Membrane: An Interface‐Engineered Heterojunction for High‐Efficiency Electrocatalytic Nitrogen Reduction

Abstract: Developing noble‐metal‐free electrocatalysts is important to industrially viable ammonia synthesis through the nitrogen reduction reaction (NRR). However, the present transition‐metal electrocatalysts still suffer from low activity and Faradaic efficiency due to poor interfacial reaction kinetics. Herein, an interface‐engineered heterojunction, composed of CoS nanosheets anchored on a TiO2 nanofibrous membrane, is developed. The TiO2 nanofibrous membrane can uniformly confine the CoS nanosheets against agglome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(59 citation statements)
references
References 39 publications
(33 reference statements)
0
59
0
Order By: Relevance
“…Finally,t he NO x contamination was spectrophotometrically examined, since the concentration of NO 2 À is in alinear relationship with the absorbance at 540 nm ( Figure S23). [9] TheU V-vis spectrum of the electrolyte after being fed with 15 N 2 for 2his compared with that fed with 14 N 2 ,a ss hown in Figure S24. It is found that the two Angewandte spectra are nearly superposed, and there is no NO 2 À detected in both cases,thus excluding the possible NO x contamination in the feed gas.…”
Section: Resultsmentioning
confidence: 99%
“…Finally,t he NO x contamination was spectrophotometrically examined, since the concentration of NO 2 À is in alinear relationship with the absorbance at 540 nm ( Figure S23). [9] TheU V-vis spectrum of the electrolyte after being fed with 15 N 2 for 2his compared with that fed with 14 N 2 ,a ss hown in Figure S24. It is found that the two Angewandte spectra are nearly superposed, and there is no NO 2 À detected in both cases,thus excluding the possible NO x contamination in the feed gas.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 To realize a green and sustainable strategy for N 2 xation, electrochemical reduction of N 2 has recently attracted much attention, being an environmentally friendly route involving mild conditions. [8][9][10] To date, a number of catalysts have been developed for the NRR, including noble metals, [11][12][13] transition metals, 14,15 metalfree materials, [16][17][18] metal-C composite materials [19][20][21] and Au-Fe 3 O 4 . 22 These catalysts have demonstrated potential applications in the NRR with improved FE and NH 3 yield.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanoplating can further improve the structural integrity and conductivity of CoS@TiO 2 heterojunction. [62] Therefore, the C@CoS@TiO 2 electrocatalyst achieves a high ammonia yield (8.09 × 10 −10 mol s −1 cm −2 /49.51 µg cm −2 h −1 ) and Faradaic efficiency (28.6 %) at −0.55 V versus RHE. The electrocatalysts used in electrochemical NH 3 synthesis to date include precious metals such as Ru, Au, Pd, and Pd, non-noble metals such as Ni, Cu, and Fe, and carbon-based materials.…”
Section: Interface Between Metal (Compound) and Metal Compoundmentioning
confidence: 92%
“…For example, CoS nanosheets can be anchored on an active matrix-flexible TiO 2 nanofiber membrane. [62] The tight coupling between CoS and TiO 2 makes the charge transfer between the two easy, thus achieving fast reaction kinetics at the heterogeneous interface (Figure 6a). Carbon nanoplating can further improve the structural integrity and conductivity of CoS@TiO 2 heterojunction.…”
Section: Interface Between Metal (Compound) and Metal Compoundmentioning
confidence: 99%